Magnetic transformation of Mn from anti-ferromagnetism to ferromagnetism in FeCoNiZMnx (Z = Si, Al, Sn, Ge) high entropy alloys. (30th March 2021) - Zhang, Bin; Duan, Yuping; Zhang, Haifeng; Huang, Shuo; Ma, Guojia; Wang, Tongmin; Dong, Xinglong; Jia, Nan
Abstract: We design high entropy alloys (HEAs) with different induction elements (Si/Al/Sn). In order to keep the crystal structure invariant and to investigate how the increment in saturation magnetization ( M s ) is caused only by the change of electron spin state, each set of HEAs contains a different amount of Mn. Synergistic effects among induction elements that induce the magnetic transformation of Mn from anti-ferromagnetism to ferromagnetism are found. M s of added Mn reduces when a particular induction element (Si0.4 /Al0.4 /Sn0.4 ) exists, while a larger increment of M s appears when two induction elements coexist, Si0.4 Al0.4 (25.79 emu/g) and Sn0.4 Al0.4 (15.43 emu/g). This is reflected in the microcosmic magnetic structure for the emergence of closed domains due to large demagnetization energy, which is confirmed by the Lorentz transmission electron microscope (LTEM) data. The calculated magnetic moments and the exchange integral constants from density functional theory based on the Exact Muffin-Tin Orbits formalism reveal that the magnetic state and the strength of ferromagnetic and anti-ferromagnetic coupling determine the variation of M s in different chemical environments. The difference in energy levels of coexisting multiple induction elements also leads to a larger increment of M s, Si0.4 Al0.4 Sn0.4 (29.78 emu/g), and Si0.4 Al0.4 Ge0.4 Sn0.4 (31.00 emu/g).